Eﬀect of transplanting dates on incidence of brinjal (Solanum melongena) shoot-and fruit-borer [Leucinodes orbonalis (Guenee)] - Chiranjiv; S M Haldhar; K I Singh; L N K Singh; Pranita Roy; S L Choudhary (Current Horticulture, 2025)
The ﬁeld experiment was conducted to study the incidence of brinjal (Solanum melongena L.) shoot-and fruit-borer [Leucinodes orbonalis (Guenee)] on diﬀerent transplanting dates at the College of Agriculture, CAU, Imphal, during 2021-22. The incidence of L. orbonalis on brinjal was noticed on diﬀerent dates. The third transplanted crop recorded relatively higher shoot damage with a mean of (25.9 per cent), followed by the second, fourth and ﬁrst transplanted crop with a mean of, 20.7, 16.5 and 11.7 per cent, respectively. Similarly, third transplanted crop recorded highest mean fruit damage (25.0 per cent on a number basis and 23.40 per cent on a weight basis), followed by second, fourth and ﬁrst transplanted crop recorded with mean fruit damage (21.7 per cent on a number basis and 20.8 per cent on weight basis, 18.0 per cent on number basis and 16.7 per cent on weight basis and 12.2 per cent on number basis and 11.9 per cent on a weight basis).